EFFECT OF BENIGN PROSTATIC HYPERPLASIA ON MORPHOLOGICAL CHANGES IN THE WALL OF THE BLADDER - Shmulichenko, O.V. (The Ukrainian Scientific Medical Youth Journal, 2017)
Benign prostatic hyperplasia (BPH) is the most common cause of bladder outlet obstruction in men, but not the only one. The number of patients with prostatic hyperplasia in the world and in Ukraine is constantly increasing [2]. According to the Institute of Urology of the Academy of Medical Sciences of Ukraine, the prevalence of BPH in Ukraine in 2013 was 1132.9 per 100 thousand adult male population. [9]. A hyperplastic prostate creates an obstacle to the outflow of urine from the bladder, including not only a mechanical factor - compression, deformation, erroneous lengthening of the proximal urethra and a change in the urethrovesical angle, but also a circulatory disorder. A close analysis of the results of examination of patients with prostate hyperplasia at various stages of the disease forces us to pay attention to the presence of morphological changes in the tissues of the bladder. [3].